Public Health Policy at Scale: Impact of a Government-Sponsored Information Campaign on Infant Mortality in Denmark - Onur Altindag; Jane Greve; Erdal Tekin (Institute of Labor Economics (IZA), 2022)
We evaluate the impact of a nationwide public health intervention on deaths from sudden infant death syndrome (SIDS), using population data from Denmark in a regression discontinuity research design. The information campaign–implemented primarily through a universal nurse home visiting program–reduced infant mortality by 17.2 percent and saved between 11.6-13.5 lives over 10,000 births. The estimated effect sizes are 11-14 times larger among low birthweight and preterm infants relative to the overall population. Improvement in infant mortality is concentrated among those with low socio-economic status and with limited access to health information, thereby reducing health inequities at birth.
Keywords: I12; I24; I18; 330; SIDS; information campaign; infant mortality; Denmark